Treatment of the subject of the small economies in the FTAA process (SELA CaracasVE, 1996)
Details the technical assistance or training activities identified by the FTAA working groups which have been carried out or are scheduled. Looks at regional and international organizations technical assistance programmes which are under way or scheduled, and technical assistance offered by countries of the hemisphere.
DC